A FORMAÇÃO DO PROFESSOR DE MATEMÁTICA EM INTERFACE COM O PIBID – PROGRAMA INSTITUCIONAL DE BOLSA DE INICIAÇÃO À DOCÊNCIA: AS REPRESENTAÇÕES DE LICENCIANDOS E SUPERVISORES - PUCETTI, SILVANA (2016)
This thesis investigates the initial training of mathematics teachers, with reference to discussions and in-depth analysis of the route on this training in Brazil on public policy Mathematics teacher training interfaced with the crisis of degrees and also on the ideas and actions that support the PIBID – Institutional Program Initiation Grant to Teaching and representations of experiences with this program of undergraduate and supervisors (teachers from partner public schools), through Subproject Mathematics, developed into a HEI – higher education institution, community, located in the Greater ABC Paulista region. The reference question pervaded by this research was: "Representations of undergraduate and Supervisors on the development of Subproject Mathematics/PIBID point to effective contributions that denote a more solid formation of licensing (surpassing the theoretical and practical distance) so that the same motive for professional integration in public schools? ". The PIBID is a project of the Federal Government, funded by the Higher Education Personnel Improvement Coordination (CAPES), which promotes the link between higher education and public schools in order to promote and encourage students of Undergraduate courses for future exercise of the profession. Preliminarily, it is presented an overview of the initial training of the mathematics teacher in the interface between mathematics teacher training for Public Policy and the crisis of degrees, the main authors of reference: Imbernon (2000); Tardif (2008); Valente (1997); D'Ambrósio (1996); Romanelli (2001); Fischmann (2014); Gatti (2010); Bahia (2015); Carlos Chagas Foundation – FCC (2014); Bahia and Souza (2013; 2014); Libâneo (2008); Nóvoa (2009); Franco (2012); Pimenta and Lima (2010), among other authors established in the area. We also conducted a field research with a view to the observations and analysis of the actions taken by the Mathematics Sub-project in the period 2014/2015, the IES investigated. Initially, we have the collaboration of 33 undergraduates participating in the Mathematics Sub-projects in 2014 for the application of a questionnaire with closed questions (for profile) and open questions (on the development of PIBID actions). In order to broaden and deepen some discussions, we selected 6 licensees (among the 33 who answered the questionnaire) and invite the two supervisors accompanying these six undergraduate schools at the time to conduct interviews with a pre-established script. The development of instruments for data collection, the interviews and data analysis, as were references Szymanski (2010) and Franco (2003). After the research application process, there were tabs and data analysis, which revealed the following results: (1) the evaluation of PIBID is strong across the country, as studies by other researchers and in the unanimous opinion of respondents in this work; (2) in view of the subject there is a direct link between improvements applied to teacher education in higher education and the improvement of the Brazilian Basic Education; (3) the approach of the University and the school is important for the improvement of initial teacher education and, especially, the Mathematics teachers as resources and teaching practices can contribute to the building of a higher standard of personal safety and professional to the licensees and therefore in better levels of education; (4) respondents recognize the value of methodologies guided in different ways of teaching mathematics as a means for understanding the construction of mathematical knowledge; and (5) the PIBID in Mathematics Sub-projects has contributed to improving the teaching of mathematics and seeks to ensure the motivation for the professional integration of current undergraduates in public schools because 84% of study subjects express the intention to remain in public schools after graduation, although this rate can only be proven in the future.